Manajemen Informasi Kurikulum Bahasa Arab - Nur Mufida Ramadhanisnaini (Sekolah Tinggi Ilmu Tarbiyah Ibnu Sina Malang, 2018)
In Arabic language curriculum management, there are information resources which should be maintained to be a basic consideration for decision makers in solving problems relating to the implementation of the Arabic language curriculum in educational institutions. This article discusses the information resource, and its role in the implementation of the Arabic language curriculum, also the concept of information management curriculum of Arabic language. Information has a strategic role in the activities: (1) the implementation of the curriculum, both schools-grade and class-level; (2) Monitoring the curriculum; (3) the assessment and improvement of the curriculum. Through the activities of information management, information resources can be processed and stored, in a system called MIS (Management Information Systems), to prepare and facilitate decision making. Thus, information resources can be contributed effectively to improve the implementation of Arabic language curriculum in the future.